1993
DOI: 10.1182/blood.v81.2.399.399
|View full text |Cite
|
Sign up to set email alerts
|

Liver-derived fetal hematopoietic stem cells selectively and preferentially home to the fetal bone marrow

Abstract: In the course of ontogeny, the homing site for the hematopoietic stem cells (HSC) moves with certain predictability from the yolk sac to the liver/spleen and then to the marrow. The pattern of this migration has thus far been established mostly on a morphologic basis. To delineate further the course of this migration and to gain insight into its possible mechanism, we used in utero transplantation of allogeneic or xenogeneic HSC in preimmune sheep fetuses. Sex chromosome, type of hemoglobin, and species-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(35 citation statements)
references
References 0 publications
1
33
0
1
Order By: Relevance
“…The preferential adhesion of fetal liver HPP-CFC to bone marrow stroma, observed in the present investigation, could be ascribed to the natural migration of fetal liver stem cells to the bone marrow in vivo. This observation is consistent with reports of selective adhesion and homing of sheep fetal liver stem cells to the bone marrow when injected into fetuses between 60 and 80 d of gestation even though the fetal liver was the main site of haemopoiesis at this stage (Zanjani et al, 1993). These authors proposed the existence of a hierarchy of homing sites, in which the bone marrow has the highest affinity for the homing of transplanted haemopoietic stem cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The preferential adhesion of fetal liver HPP-CFC to bone marrow stroma, observed in the present investigation, could be ascribed to the natural migration of fetal liver stem cells to the bone marrow in vivo. This observation is consistent with reports of selective adhesion and homing of sheep fetal liver stem cells to the bone marrow when injected into fetuses between 60 and 80 d of gestation even though the fetal liver was the main site of haemopoiesis at this stage (Zanjani et al, 1993). These authors proposed the existence of a hierarchy of homing sites, in which the bone marrow has the highest affinity for the homing of transplanted haemopoietic stem cells.…”
Section: Discussionsupporting
confidence: 91%
“…In utero transplantation techniques combined with cell marker studies have enabled investigation of ontogenic haemopoietic cell migration in vivo (Zanjani et al, 1991(Zanjani et al, , 1993Clapp et al, 1995;Hendrikx et al, 1996). Zanjani et al (1993) observed selective adherence of sheep fetal liver cells to bone marrow derived stroma and suggested that a hierarchy of homing sites may exist in which bone marrow has a higher affinity than either fetal liver or spleen. Retrovirally marked rat fetal liver cells have been demonstrated to home to the medullary cavity where they proliferated and gave rise to progenitors in new-born and adult rats (Clapp et al, 1995).…”
mentioning
confidence: 99%
“…Homing of circulating blood cells to the BM is a key event not only in BM transplantation, but also for seeding of the BM during fetal development. Studies in sheep and mice have shown that hematopoiesis in the BM occurs only after birth, whereas fetal blood is generated in the yolk sac, fetal liver (FL), and aorta-gonads-mesonephros region [40][41][42]. In the mouse, pluripotent circulating HPC begin to colonize the nascent BM before day 14 of gestation [42].…”
Section: Physiological Significance Of Bm-specific Endothelial Adhesimentioning
confidence: 99%
“…The engraftment of mouse fetuses with fetal liver cells resulted in L TMR throughout adult life (Fleischman et al 1982). Zanjani et al (1993) infused fetal sheep with fetal liver cells and found that the relative representation of the donor cells increased in bone marrow and decreased in the liver with increasing gestational age of the recipient. Although these observations may be indicative of developmentally regulated migration.…”
Section: The Tr Ansition To Adult Hematopoiesismentioning
confidence: 99%